2019
DOI: 10.1177/1063426619838539
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Ethnic Measurement Equivalence of the Children’s Depression Inventory Among Youth in Foster Care

Abstract: Previous research has indicated differences in the presentation and measurement of depressive symptoms across ethnic groups. In the current study, we examined the factor structure of the Children’s Depression Inventory in an ethnically diverse sample of adolescents in foster care ( n = 346; Mage = 13.13 years, SD = 2.18 years) and examined the configural invariance of the measure across ethnic groups. Findings indicated a two-factor structure in the total sample. Furthermore, configural invariance was not supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The CDI has shown good test–retest reliability, internal consistency, and construct validity in nonclinical populations (Sitarenios & Kovacs, 1999) and is the most frequently used scale for the study of child and adolescent depression (Twenge & Nolen-Hoeksema, 2002). Reliability of the CDI with Latinx adolescents has been supported by previous research (Gonzales-Backen et al, 2020). In the present study, item ratings were averaged, with high scores representing higher levels of depressive symptoms.…”
Section: Methodssupporting
confidence: 56%
See 2 more Smart Citations
“…The CDI has shown good test–retest reliability, internal consistency, and construct validity in nonclinical populations (Sitarenios & Kovacs, 1999) and is the most frequently used scale for the study of child and adolescent depression (Twenge & Nolen-Hoeksema, 2002). Reliability of the CDI with Latinx adolescents has been supported by previous research (Gonzales-Backen et al, 2020). In the present study, item ratings were averaged, with high scores representing higher levels of depressive symptoms.…”
Section: Methodssupporting
confidence: 56%
“…In contrast, findings about the association between acculturative stress and externalizing behaviors among Latinx are inconsistent. Although it is expected that Latinx adolescents would engage in externalizing behaviors to manage stress (Gil et al, 2000) or to express frustration, and to assert power against perceived discrimination (Nair et al, 2013), research does not consistently support the direct association between acculturative stress and externalizing behaviors (Umaña- Taylor et al, 2011). A few studies show that acculturative stress is indirectly associated with externalizing behaviors through a mediating variable such as self-esteem (Schwartz et al, 2007) or familism (Gil et al, 2000).…”
Section: Acculturative Stress Depressive Symptoms and Delinquent Beha...mentioning
confidence: 99%
See 1 more Smart Citation
“…Item scores are summed for a composite score, with higher scores indicating greater symptom severity. The CDI has been used extensively among diverse research and clinical samples of children and adolescents and has demonstrated strong psychometric properties (Gonzales-Backen et al, 2020; Twenge & Nolen-Hoeksema, 2002). Internal consistency in the current sample was high (α = .87).…”
Section: Methodsmentioning
confidence: 99%